Metabolic niches in the rhizosphere microbiome: dependence on soil horizons, root traits and climate variables in forest ecosystems - Maitra, Pulak; Hrynkiewicz, Katarzyna; Szuba, Agnieszka; Jagodziński, Andrzej M.; Al-Rashid, Jubair; Mandal, Dipa; Mucha, Joanna (Frontiers in Plant Science, 2024)
Understanding belowground plant-microbial interactions is important for biodiversity maintenance, community assembly and ecosystem functioning of forest ecosystems.Consequently, a large number of studies were conducted on root and microbial interactions, especially in the context of precipitation and temperature gradients under global climate change scenariosscinerios. Forests ecosystems have high biodiversity of plants and associated microbes, and contribute to major primary productivity of terrestrial ecosystems. However, the impact of root metabolites/exudates and root traits on soil microbial functional groups along these climate gradients is poorly described in these forest ecosystems. The plant root system exhibits differentiated exudation profiles and considerable trait plasticity in terms of root morphological/phenotypic traits, which can cause shifts in microbial abundance and diversity.The root metabolites composed of primary and secondary metabolites and volatile organic compounds that have diverse roles in appealing to and preventing distinct microbial strains, thus benefit plant fitness and growth, and tolerance to abiotic stresses such as drought. Climatic factors significantly alter the quantity and quality of metabolites that forest trees secrete into the soil. Thus, the heterogeneities in the rhizosphere due to different climate drivers generate ecological niches for various microbial assemblages to foster beneficial rhizospheric interactions in the forest ecosystems. However, the root exudations and microbial diversity in forest trees vary across different soil layers due to alterations in root system architecture, soil moisture, temperature, and nutrient stoichiometry. Changes in root system architecture or traits, e.g. root tissue density (RTD), specific root length (SRL), and specific root area (SRA), impact the root exudation profile and amount released into the soil and thus influence the abundance and diversity of different functional guilds of microbes. Here, we review the current knowledge about root morphological and functional (root exudation) trait changes that affect microbial interactions along drought and temperature gradients. This review aims to clarify how forest treesplants adapt to challenging environments by leveraging their root traits to interact beneficially with microbes. Understanding these strategies is vital for comprehending plant adaptation under global climate change, with significant implications for future research in plant biodiversity conservation, particularly within forest ecosystems.